2016
DOI: 10.1007/s13277-016-4785-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of carbonic anhydrase potentiates bevacizumab treatment in cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA) is a unique liver cancer subtype with an increasing incidence globally. The lack of specific symptoms and definite diagnostic markers results in a delayed diagnosis and disease progression. Systemic chemotherapy is commonly selected for advanced CCA even though its advantages remain unknown. Targeted therapy, especially anti-vascular endothelial growth factor (VEGF) therapy, is promising for CCA; however, improvements in the therapeutic regimen are necessary to overcome subsequent resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…For example, targeting HIF1α increases the efficacy of bevacizumab in neuroblastoma xenografts [38]. A similar effect has also been reported when bevacizumab is combined with acetazolamide [14] [39]. More importantly, such strategies are also tested in clinical trials [37].…”
Section: Discussionmentioning
confidence: 83%
“…For example, targeting HIF1α increases the efficacy of bevacizumab in neuroblastoma xenografts [38]. A similar effect has also been reported when bevacizumab is combined with acetazolamide [14] [39]. More importantly, such strategies are also tested in clinical trials [37].…”
Section: Discussionmentioning
confidence: 83%
“…The state of hypoxia and acidity of the tumor microenvironment represents a challenge for chemotherapeutic agents [95][96][97][98][99][100]. Carbonic anhydrase inhibitors were found to prohibit cancer metastasis; this was mainly linked to increasing the sensitivity of the cancer cells to the anti-angiogenic agents [98]. It was also shown that treating cells with CAIX and CAXII inhibitors promote the susceptibility to radiotherapy-induced apoptosis [97].…”
Section: Carbonic Anhydrase Enzymementioning
confidence: 99%
“…Therefore, in addition to canonical TGF-β target genes, VEGF represents the first proangiogenic factor regulated by TGF-β1 through Sp1. Molecules such as Bevacizumab show promising results because of their ability to neutralize VEGF-induced angiogenic effect which leads to a decrease of tumor progression [93]. Vandetanib, an inhibitor of both VEGFR and EGFR factors, reveals anti-tumor and anti-metastatic properties [87], while Apatinib, which selectively suppresses VEGFR2 signaling and results in anti-apoptosis action, is proven as one of the candidates in the treatment of CCA [94].…”
Section: Vascular Endothelial Growth Factors (Vegfs) and Placental Grmentioning
confidence: 99%